Responses to Backward Masked Faces with and without Conscious Awareness - Tsikandilakis, Myron (2020)
Previous research has suggested that we can experience physiological arousal and emotional changes in response to emotional faces without conscious awareness. This line of research has also provided evidence to support that subordinate facial characteristics such as emotion, attractiveness and cultural background can be reported in the absence of conscious awareness. These traits are suggested to confer evolutionary important sociobiological value and therefore, the suggestion has been put through that they can be appraised automatically and involuntarily. The purpose of this mechanism is to enable us to respond to important environmental cues without relying on slow cortical systems for the initiation or inhibition of significant survival and social-related actions. Although a considerable number of publications support this notion, an equally substantial number of research papers has challenged the evidence that suggest that we can emotionally and physiologically respond to subliminal cues. The latter line of research suggests that the current experimental model for the assessment of subliminality includes important limitations relating to the implementation of subliminal presentations, the assessment of stimuli visibility and the statistical analysis of participant responses. In the current studies, we address these issues using a novel method for the assessment of subliminality. In the first three experimental chapters, we present a method for assessing skin conductance, heart rate, facial emotional responses and engagement task responses to backward masked emotional faces. This method includes defining individual thresholds for subliminal perception for each participant and for each facial expression using both hit rates and unbiased receiver operating characteristics. We also employ Bayesian analysis for the assessment of subliminal perception, trial-by-trial physiological assessment of hits (correct detection/discrimination) and misses (incorrect detection/discrimination) for signal detection and discrimination performance, and trial-by-trial physiological assessment of confidence responses for hits and misses for awareness. In the final two experimental chapters, we use part of this assessment method to test whether facial characteristics, such as attractiveness and cultural background, can be appraised without conscious awareness. Our findings suggest that using the current assessment method, physiological and emotional changes, and the appraisal of facial characteristics, such as attractiveness and cultural background, can occur in response to brief masked faces only when the participants are able to report conscious face-detection meta-awareness. Our findings shed doubt on the “established” notion that we can be physiologically influenced by subliminal emotion, and counter-suggest that even though brief faces can influence our physiological and appraisal responses, this effect is accompanied by conscious awareness.